2012
DOI: 10.1080/02642069.2010.545392
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotions displayed and personal selling on customer behaviour intention

Abstract: The impact of employee performance on customer behavioural intentions and consumption behaviour is important to service marketers. In many service settings, service organizations require emotional display and personal selling to stay competitive in todays market. Based on a review of service literature, this study investigates the effect of emotions displayed and personal selling on customer purchase amount and re-patronage intention in convenience-goods retail service settings. This work applies mystery shopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 72 publications
1
11
0
1
Order By: Relevance
“…The corresponding results were found by Hill and Alexander (2016) , Ryu and Han (2010) , Ryu and Jang (2008) as well as Santouridis and Trivellas (2010) . Later on, Beneke et al (2013) ; Jakpar et al (2012) ; Kafetzopoulos et al (2015) ; Vera (2015) ; Verhoef and Lemon (2013) ; Wang et al (2012) and Prakash et al (2017) also confirmed equivalent findings that product quality is positively related to customer satisfaction.…”
Section: Discussionmentioning
confidence: 67%
“…The corresponding results were found by Hill and Alexander (2016) , Ryu and Han (2010) , Ryu and Jang (2008) as well as Santouridis and Trivellas (2010) . Later on, Beneke et al (2013) ; Jakpar et al (2012) ; Kafetzopoulos et al (2015) ; Vera (2015) ; Verhoef and Lemon (2013) ; Wang et al (2012) and Prakash et al (2017) also confirmed equivalent findings that product quality is positively related to customer satisfaction.…”
Section: Discussionmentioning
confidence: 67%
“…The focal retailer in this study provided weekly mystery shopper reports that coincided with the eight-month scanner data, later narrowed down to the 10-week period under study. Similar to previous research that used mystery shopper data (Finn & Kayande, 1999;Wang, Tsai, Chen, & Chang, 2012), the data-gathering phase was conducted by trained professionals who were experienced in this type of data collection method. The team of mystery shoppers were full-time employees of the focal retailer.…”
Section: Mystery Shopper Datamentioning
confidence: 99%
“…Although impactful in the insights that it can improve service quality, the North American MSPA organization (2014) cautions that the MC survey is not exclusive or sufficient, but a complementary method to other research tools. In the scientific literature, MC has been applied in several service research contexts: health (Gosselt et al, 2007;Young et al, 2009;Glasier et al, 2010;Wong et al, 2012), banking (Tarantola et al, 2012), family planning (León et al, 1994), hospitality tourism and transportation (Nathanail, 2008;Butcher et al, 2009) and retailing (Finn and Kayandé, 1999;Gómez et al, 2011;Wang et al, 2012). Table I combines several definitions of MC surveys.…”
Section: Mystery Client Conceptmentioning
confidence: 99%
“…Behavioral dimensions of service operations should not be undermined, as regardless of how mechanistically employees are programmed to manage their activities, there are always in some extent personal contact and interaction with someone (Croson et al, 2013). Both (mystery) clients and employees express and react emotionally which may influence their response/performance (Van Eerde and Peper, 2008;Wang et al, 2012;Urda and Loch, 2013).…”
Section: Mystery Client Potential Individual Differencesmentioning
confidence: 99%